Replication of Losida for Organic Waste Management in Yogyakarta - Puspitasari, Fransiska Hernina; Anindyajati, Adhi (Society : Jurnal Pengabdian Masyarakat, 2024)
Proper urban waste management in Yogyakarta, Indonesia, has emerged as a critical challenge, with upsurge in unmanaged waste levels resulting in devastating environmental and health problems. With the new waste management initiatives sprouting up, community programs and local universities have developed many in the recent past, keeping in mind the greener alternative in a bid to reduce their environmental footprints and embrace sustainability. This paper describes a community service project in designing and constructing losida (kitchen waste bin) that conducts several activities. The project activities are carried out with several local waste banks and waste facilitators from the City of Yogyakarta. The project activity was designing the losida, manufacturing the losida, education of kitchen waste with losida, presentation on household waste processing, and handover the losida to Bank Sampah Masdarling members. The output of project has implemented to create ten units of losida and has been channeled to the waste bank's members. In addition, the workshop of organic waste processing has been carried out in the local community and campus. This research concludes that, in one case, academies and community programs are in need of engaging in more collaborative activities to play significant roles in dealing with urban waste management problems in Yogyakarta, whereas, in another case, it is established that such collaborative activities have brought a significant stride in a sustainable and green waste management paradigm, with high potential for emulation elsewhere in urban centers facing waste management crises.